If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -1 + p = 10p + -9 Reorder the terms: -1 + 8p + p = 10p + -9 Combine like terms: 8p + p = 9p -1 + 9p = 10p + -9 Reorder the terms: -1 + 9p = -9 + 10p Solving -1 + 9p = -9 + 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. -1 + 9p + -10p = -9 + 10p + -10p Combine like terms: 9p + -10p = -1p -1 + -1p = -9 + 10p + -10p Combine like terms: 10p + -10p = 0 -1 + -1p = -9 + 0 -1 + -1p = -9 Add '1' to each side of the equation. -1 + 1 + -1p = -9 + 1 Combine like terms: -1 + 1 = 0 0 + -1p = -9 + 1 -1p = -9 + 1 Combine like terms: -9 + 1 = -8 -1p = -8 Divide each side by '-1'. p = 8 Simplifying p = 8
| 2z-3=53+9z | | 4+3y=-12 | | -17=4x+12-9x | | 3x-5/x-1=3x-2/x+2 | | -0.4p=0.2p+9 | | -7x+1=6 | | 8/3-2 | | 7f-8=2 | | 2x5/2+5x3/2=7x1/2 | | 7/12+1/4 | | 13/85.8 | | -c+4=-2c | | x/2+5=-12 | | -8x-2=24-9x | | 45/34a=23.3+46a | | 5.6q-3.4-4.9q=0.3q-2.3 | | 3-3(3n-3)=39 | | 3a+9b+-5a+15b= | | 5/9=h/30 | | -8x-2=24-9 | | 8+16p^2=33 | | 85.5/13 | | 9x-4=5x+4 | | 4t+5=-10+t | | v-15=9 | | 63(x-3)=9(x+3) | | 2(x+4)=3x+5 | | 7a+-9b+3a+9b= | | 5x+9=-3 | | O(5)=2(5)-1 | | 8m-7=21+m | | 12q-7=-3q+8 |